Informality and the impact of COVID-19 on maize value chains in Uganda: Key findings and policy implications - Nabwire, Leocardia; Van Campenhout, Bjorn (International Food Policy Research Institute, 2022)
This policy note summarizes results of a study on the impact of COVID-19 on maize value chains in Uganda, which are characterized by a high degree of informality. We use a stack survey consisting of 1525 smallholder maize farmers, 341 informal traders, and 174 millers that were surveyed in-person in 2019 as the basis for follow-up telephone interviews in 2020 and 2021. We find that the impact of COVID-19 and associated measures manifests itself more downstream the value chain (at the level of the traders and particularly the millers). Closures and reductions in volumes passing through the chain seemed limited but worsen as the pandemic persists. Government measures such as a reduction of interest rates seemed to have brought some relief for traders and millers. However, all value chain actors report substantial reductions in maize revenues, household income and food security, as actors in informal value chains seem to rely on various activities to make ends meet. As a result, informal value chains such as maize in Uganda may be less able to adapt to common shocks in the long run. The appropriate policy response therefore would be to supplement some of the mitigating policies targeting businesses with more long run social protection policies to also benefit value chain actors upstream.